2019
DOI: 10.1016/j.virusres.2019.197767
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of Sambucus FormosanaNakai ethanol extract and related phenolic acid constituents against human coronavirus NL63

Abstract: Human coronavirus NL63 (HCoV-NL63), one of the main circulating HCoVs worldwide, causes respiratory tract illnesses like runny nose, cough, bronchiolitis and pneumonia. Recently, a severe respiratory illness outbreak of HCoV-NL63 has been reported in a long-term care facility. Sambucus FormosanaNakai, a species of elderberry, is a traditional medicinal herb with anti-inflammatory and antiviral potential. The study investigated the antiviral activity of Sambucus FormosanaNakai stem ethanol extract and some phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 35 publications
0
107
1
1
Order By: Relevance
“…Moreover, based on historical records of the effect of antiviral herbs on SARS and influenza H1N1, Chinese herbal formulas could be an alternative approach for the prevention of SARS-CoV-2 in a high-risk population [107], if no scientifically based therapeutics are available. It was found that Sambucus formasana Nakai exhibited a strong antiviral effect against human coronavirus NL63 [108].…”
Section: Control and Treatment Of Covid-19 Infectionmentioning
confidence: 99%
“…Moreover, based on historical records of the effect of antiviral herbs on SARS and influenza H1N1, Chinese herbal formulas could be an alternative approach for the prevention of SARS-CoV-2 in a high-risk population [107], if no scientifically based therapeutics are available. It was found that Sambucus formasana Nakai exhibited a strong antiviral effect against human coronavirus NL63 [108].…”
Section: Control and Treatment Of Covid-19 Infectionmentioning
confidence: 99%
“…In addition, tetrandrine activated the p38MAPK pathway in MRC-5 cells, improving the aforementioned host response. Weng et al (2019) tested the ethanolic extracts of Sambucus formosana (elderberry) stems against the human coronavirus strain HCoV-NL63, finding quite high efficacy (EC 50 of 1.17 ± 0.75 μg/mL) for viral yield reduction. With further investigation of the phenolic composition of the extracts and antiviral assays performed on the main individual phenolic acids present, caffeic acid (Fig.…”
Section: Inhibitors Of Other Human Coronovirusesmentioning
confidence: 99%
“…Elderberry (Sambucus nigra) is hypothesized to have antiviral properties because of its ability to modulate inflammatory cytokines 42 and has been tested both in vitro [43][44][45][46][47] and in vivo against varying viruses. [48][49][50][51][52] At the time of writing, there are no published studies evaluating the use of elderberry and COVID-19.…”
Section: Elderberrymentioning
confidence: 99%